Doing institutions. A dialectic reading of institutions and social practices and its relevance for development geography - Etzold, Benjamin; Jülich, Sebastian; Keck, Markus; Sakdapolrak, Patrick; Schmitt, Thomas; Zimmer, Anna (ERDKUNDE, 2012)
Twelve years after the discussions on development and institutions at the meeting of the Geographischer Arbeitskreis Entwicklungstheorien (GAE 2000) in Zürich, this paper seeks to put institutions back on the research agenda in development geography. The authors explore recent trends in institutional theory and propose a dialectic understanding of “doing institutions” that positions social actors and their everyday practices at the center of institutional analysis. Institutions are the socially (re-)produced rules that enable, constrain and give meaning to the social practices of actors. Actors make institutions; at the same time institutions make actors do certain things. Based on this foundation, three central aspects of the institutional debate are elaborated: Institutional plurality, the legitimacy of institutions, and the role of the state. Two case studies from recent research in South Asia illustrate aspects of the conceptual considerations. The article ends with an outlook on the implications of “doing institutions” for future research in development geography.